Governmental Non-Pharmaceutical Interventions during the COVID-19 Pandemic and the COPD Exacerbation and Respiratory Infection Rate in Patients with Alpha-1 Antitrypsin Deficiency - Naomi Nanke Kappe; Noga Alagem; Naveh Tov; Jan Stolk (COPD, 2023)
During the COVID-19 pandemic the number of hospital admissions due to chronic obstructive pulmonary disease (COPD) exacerbations was significantly reduced. The reason for this decline is not fully understood. Governmental non-pharmaceutical interventions (NPI’s), an increase in community treated exacerbations, or healthcare avoidance by patients, are potential reasons. For the current study, the impact of Dutch governmental NPI’s on the COPD exacerbations and respiratory infections rate in patients with severe alpha-1 antitrypsin deficiency (AATD) was analyzed. The patients participated in the NCT04204252 study, a randomized controlled trial evaluating the efficacy and safety of inhaled alpha-1 antitrypsin. Data collected in the time-period from March 2020 until February 2022 was analyzed. In this period the Dutch government imposed variable NPI’s to contain the spread of SARS-CoV-2. Patients were required to document their daily symptoms in an electronic diary. The strictness of the governmental NPI’s was measured by the COVID-19 Stringency Index. 19 patients participated in this study during the analysis period. A total of 40 respiratory infections and COPD exacerbations occurred. The Spearman’s correlation coefficient of the monthly average COVID-19 Stringency Index and respiratory infections and COPD exacerbations rate was −0.316 (p = 0.132). When months known for a low respiratory infection rate were excluded, the correlation coefficient was −0.625 (p = 0.010). This study showed a significant negative correlation between the COPD exacerbations and respiratory infection rate and the COVID-19 Stringency Index in patients with AATD related COPD in the autumn-winter months.